Effect of Sericin Supplementation During In Vitro Maturation on the Maturation, Fertilization and Development of Porcine Oocytes. Issue 2 (28th January 2014) - Do, LTK; Namula, Z; Luu, VV; Sato, Y; Taniguchi, M; Isobe, T; Kikuchi, K; Otoi, T
Contents This study aimed to examine the effects of sericin supplementation during in vitro oocyte maturation on the nuclear maturation, fertilization and development of porcine oocytes. Cumulus‐oocyte complexes (COCs) were cultured in maturation medium supplemented with 0 (control), 0.1, 0.5, 1.0, 2.5 or 5.0% sericin and were then subjected to in vitro fertilization and embryo culture. More COCs matured with 1.0% sericin underwent germinal vesicle breakdown and reached metaphase II compared with the control COCs matured without sericin (p < 0.01). The proportions of oocytes with DNA‐fragmented nuclei did not differ between the groups, regardless of the sericin level. The total fertilization rate of oocytes matured with 1.0% sericin was higher (p < 0.05) than that of oocytes matured with 0.1%, 2.5% and 5.0% sericin. Supplementation with more than 1.0% sericin decreased the DNA fragmentation index of the blastocysts compared with the control group (p < 0.05). However, the supplementation of the maturation medium with sericin had no beneficial effects on the cleavage, development to the blastocyst stage and the total cell number of the embryos. Our findings indicate that supplementation with 1.0% sericin during maturation culture may improve the nuclear maturation and the quality of the embryos but does not affect blastocyst formation.